'Symbiotic' semiconductors: unusual and counter-intuitive Ge/Si/O interactions. (9th February 2017) - George, T; Li, P W; Chen, K H; Peng, K P; Lai, W T
Abstract: Since the inception of the first transistors in the 1940s, the immense body of work on the Group IV semiconductors, Si and Ge, has spearheaded spectacular advances in modern integrated-circuit (IC) technology that has enabled a vast landscape of device applications in logic, memory, and computing. Although initially Si supplanted Ge as the material of choice for metal–oxide–semiconductor field-effect transistors, Ge-based devices are now breaking new ground. Widespread and innovative Ge-based applications exist in optoelectronics, communications, microelectro-mechanical systems, and energy harvesting/savings. On the fundamental, materials science front, while it is well known that Ge and Si are fully miscible in each other, the nature and extent of their attraction for each other has largely been unexplored. In this paper, we report a rather curious interplay between Ge and Si that occurs at high temperature (~900 °C) and that can be best described as 'symbiotic'. Each element appears to facilitate reactions in the other which would otherwise not be possible. Oxygen intersititials also appear to play a major role in these reactions. Our experimental work has allowed us to classify four distinct regimes where these reactions occur. We describe these conditions and provide the necessary theoretical explanations for these results.